PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBASIS PENILAIAN AUTENTIK TERHADAP HASIL BELAJAR SISWA - Pratiwi, Khana Fitri; Wijayati, Nanik; Mahatmanti, F. Widhi; Marsudi, Marsudi (Universitas Negeri Semarang, 2019)
Selection of learning model is influential on the success of student learning. The guided inquiry learning model is one of the student-centered learning models and emphasizes the learning process of students in finding concepts. The guided inquiry learning model based on authentic assessment makes learning activities meaningful and enables improving student learning outcomes as the student's per-stage development can be measured. This research is an experimental research using posttest-only control design. Population in this research is all students of class XI IPA SMA Negeri 1 Pabelan. The samples in this study were taken with saturated sampling. Class XI IPA 1 as experiment class and class XI IPA 2 as control class. Data collection methods used are interview, documentation test and observation methods. This study begins treatment and endsÃ‚Â posttest. Based on the result of research, the mean value of posttest of cognitive domain for experimental class is 80,28 and control class equal to 76,60. This concludes that the cognitive class experimental mean of the experimental class is better than the control class proved by t-test, that mean of the experimental cognitive learning outcomes differ significantly with the control class. Psychomotor and affective domain results with very good criteria in the experiment class more than the control class. Based on the analysis of research results can be obtained conclusion that the guided inquiry model based on authentic assessment has a positive effect on student learning outcomes.